Community‐Engaged Strategies to Promote Relevance of Research Capacity‐Building Efforts Targeting Community Organizations. Issue 5 (7th May 2015) - Cunningham, Jennifer; Miller, Stephania T.; Joosten, Yvonne; Elzey, Jared D.; Israel, Tiffany; King, Christine; Luther, Patrick; Vaughn, Yolanda; Wilkins, Consuelo H.
Abstract: Objective: The study goal is to highlight strategies for promoting relevance of research capacity‐building efforts targeting community organizations (CO)s. Methods: Two community partners, representing two COs, were invited to participate in CO research development trainings, Community Research Forums (Forum)s. Their contributions were documented via Forum document review. Forum participants, representatives from other COs, completed post‐Forum surveys to identify additional training needs and rate Forum impact relative to their training expectations. A content‐based analysis and descriptive statistics were used to summarize needs assessment‐ and impact‐related survey responses, respectively. Results: Community partners were involved in eight Forum‐related activities including marketing (planning), facilitation (implementation), and manuscript coauthorship (dissemination). Eighty‐one individuals, representing 55 COs, attended the Forums. Needs assessment responses revealed a desire for additional assistance with existing Forum topics (e.g., defining research priorities) and a need for new ones (e.g., promoting organizational buy in for research). Ninety‐one percent of participants agreed that the Forum demonstrated the value of research to COs and how to create a research agenda. Conclusions: Including community partners in all Forum phases ensured that CO perspectives were integrated throughout. Post‐Forum needs and impact assessment results will help in tailoring, where needed, future training topics and strategies, respectively.